Analysis of Variables Determining Labor Absorption in Micro and Small Industries on the Island of Java - Fika Chairunisa Azhari; Nuraini, Ida (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
Micro and small industries play a crucial role in economics. This research aims to determine the magnitude of the roles of micro and small enterprises in labour absorption on the islands of Java. The data analysis method uses panel data analysis with a random-effects model. The type of data in this research is panel data, namely a combination of cross-section and time-series data covering six provinces on the islands of Java in 2017-2022. The research results show that the variables of several industries and the production value of micro and small enterprises have a positive and significant effect on labour absorption on the islands of Java.